New records of the tribe Cerambycini (Coleoptera: Cerambycidae: Cerambycinae) from Vietnam - Quynh Nga, Cao Thi; Long, Khuat Dang; Thinh, Ta Huy (Academia Journal of Biology, 2015)
The paper listed 50 species of 18 genera belonging to the tribe Cerambycini from Vietnam, of the total 50 species there are five species newly recorded for the Vietnam’s fauna, viz. Aeolesthes (Pseudaeolesthes) pericalles Gressitt & Rondon, 1970 and one species of the genus Aeolesthes s.s. are Aeolesthes sinensis Gahan, 1890; Derolus ornatus Gressitt & Rondon, 1970; Dymasius maculatus Gressitt & Rondon, 1970; Massicus raddei (Blessig, 1872). Diagnosis of all genera are presented with notes on distribution. An illustrated key to 18 genera of the tribe Cerambycini is also provided.